Comparison of MALDI-TOF-MS and RP-HPLC as Rapid Screening Methods for Wheat Lines With Altered Gliadin Compositions - Jang, You-Ran; Cho, Kyoungwon; Kim, Sewon; Sim, Jae-Ryeong; Lee, Su-Bin; Kim, Beom-Gi; Gu, Yong Q.; Altenbach, Susan B.; Lim, Sun-Hyung; Goo, Tae-Won; Lee, Jong-Yeol (Frontiers in Plant Science, 2020)
Wheat gliadin proteins are the primary cause of celiac disease in humans. Here, we compared analytical methods to explore the genetic complexity of gliadins in the bread wheat (Triticum aestivum) cultivar 'Chinese Spring’ (CS) using aneuploid lines for chromosomes 1 and 6. We optimized matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and reversed-phase high-performance liquid chromatography (RP-HPLC) and evaluated the quality of the resulting gliadin profiles using newly available genome sequences for gliadin genes. The two major peaks in the range of 30.3–32.5 kDa with MALDI-TOF-MS included as many as 23 α/γ-gliadins estimated based on the 44 total predicted CS gliadin proteins. Thus, MALDI-TOF-MS does not provide sufficient resolution for effective gliadin profiling. By contrast, we successfully improved the resolution of RP-HPLC to obtain 34 separate peaks in the CS gliadin fraction. By comparing the gliadin profile of CS with those of the aneuploid lines, we assigned 26 peaks to chromosomes 1 and 6 - seven ω- and eight γ-gliadins encoded by chromosome 1 and eleven α-gliadins encoded by chromosome 6. These results indicate that RP-HPLC is an effective analytical method to screen wheat lines, especially those that have lost epitopes for wheat-related diseases in classical breeding or biotechnology approaches.